New perspectives, rational designs, and engineering of Tin (Sn)-based materials for electrochemical CO2 reduction - Shaikh N.S. (2023)
Minimizing greenhouse CO2 gas emissions is a primary research concern to avoid the outcome of climate crisis. Electrochemical CO2 reduction (EcCO2R) in upgraded chemicals and fuels offers a way to address CO2 emission. Because of their high efficiency, low cost, and environmental friendliness, tin (Sn)-based electrocatalysts have attracted a lot of attention. The typical methodologies to increase electrocatalytic performance and selectivity towards desired product and electrochemical CO2 reduction reaction (EcCO2R) are critically reviewed in this paper. The main objective of this review article is to explore and summarize possible Sn-based materials and composites for the application of EcCO2RR. The impact of composition engineering, nanoengineering, and mechanisms to improve electrocatalytic performance are studied. The electrochemical performance of Sn-based materials and their composites based on the overpotential, electrochemical active surface area (ECSA), Tafel slope, selectivity, turn over frequency (TOF) and chronopotentiometric/chronoamperometric stability have been explained. Thus, tin-based materials have promising perspectives as catalysts for the reduction of electrochemical CO2, with potential for further optimization and integration with renewable energy sources.